2000
DOI: 10.3141/1723-05
|View full text |Cite
|
Sign up to set email alerts
|

Uncompacted Void Content of Fine Aggregate as Quality Indicator of Materials Used in Superpave Mixtures

Abstract: The uncompacted void content of fine aggregate, or fine aggregate angularity (FAA), was introduced in the Superpave mixture design system to screen smooth or rounded fine aggregates that may result in mixtures with low rutting resistance. The assumption is that fine aggregates with lower FAA values have lower shear strength (internal friction) and lower resistance to rutting. Continued implementation and evaluation of the Superpave system has led to numerous questions regarding the validity of this assumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Most of these studies had inconsistent results, where the evaluation of the inclusion of natural sand was arbitrarily or without following a systematic procedure, and percentages of natural sands included in the mix were relatively high. This can be seen in a number of studies including [4,5,6,7,8,9,10]. The results of the aforementioned studies lack consistency since not much consideration was given to aggregates particles shapes, packing, and gradations.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies had inconsistent results, where the evaluation of the inclusion of natural sand was arbitrarily or without following a systematic procedure, and percentages of natural sands included in the mix were relatively high. This can be seen in a number of studies including [4,5,6,7,8,9,10]. The results of the aforementioned studies lack consistency since not much consideration was given to aggregates particles shapes, packing, and gradations.…”
Section: Introductionmentioning
confidence: 99%
“…Cubical-shaped particles, for example, even with 100% fractured faces, have been found not to be able to meet the FAA requirement for heavy-volume traffic even though good field performance has been observed. Additional field studies have also shown that even when the fine aggregates met the minimum FAA values, poor field performance had occurred (3)(4)(5). Therefore, further work may be needed to validate, possibly refine the use of the FAA test as a means of screening different fine aggregates for their use in HMA, provide a surrogate test method to screen fine aggregates for use in HMA, or all functions.…”
mentioning
confidence: 99%
“…Several studies have demonstrated the significant effect of fine aggregate shape properties on the mixture stability and its capability to resist rutting (e.g., 2-4). However, recent findings show that the FAA values of aggregates do not correlate well with the performance of mixtures in which they are used (5,6). These findings emphasize the importance of developing new procedures for quantifying fine aggregate shape properties based on the fundamental understanding of the different elements that make up aggregate shape.…”
mentioning
confidence: 99%